2017
DOI: 10.1038/s41598-017-07007-z
|View full text |Cite
|
Sign up to set email alerts
|

Photo-irradiated caffeic acid exhibits antimicrobial activity against Streptococcus mutans biofilms via hydroxyl radical formation

Abstract: An antimicrobial technique based on photo-oxidation of caffeic acid (CA) has recently been developed, but its effect on biofilm-forming bacteria is unknown. The present study aimed to evaluate the effect of photo-irradiated CA against Streptococcus mutans (cariogenic bacteria) biofilm as it relates to hydroxyl radical formation. S. mutans biofilms grown on hydroxyapatite disks were immersed in CA solution (0–2 mg/mL) and irradiated with LED light at wavelengths of 365, 385, and 400 nm and at irradiances of 500… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…Plants contain a number of chemicals, including phenolic acids, which have been identified as potential internal biological activity, and methods of extraction are commonly used for their recovery. Growing plant produces and accumulates a certain amount of these compounds in its tissues, and their attractiveness to solvents varies by polarity [ 34 ]. The first step in the use of phytochemicals is the extraction of bioactive compounds from plant materials.…”
Section: Discussionmentioning
confidence: 99%
“…Plants contain a number of chemicals, including phenolic acids, which have been identified as potential internal biological activity, and methods of extraction are commonly used for their recovery. Growing plant produces and accumulates a certain amount of these compounds in its tissues, and their attractiveness to solvents varies by polarity [ 34 ]. The first step in the use of phytochemicals is the extraction of bioactive compounds from plant materials.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, inactivation of S. mutans within biofilms was reported after exposure to the combination of caffeic acid (0–2 mg/mL) and light (365, 385 and 400 nm; 120–480 J/cm 2 ), with the highest inactivation (5 log CFU/mL) achieved at caffeic concentration of 2 mg/mL and blue light dosage of 480 J/cm 2 (385 nm) [ 231 ]. Other authors also reported the synergistic antimicrobial activities of blue light (400 nm) and wine grape-derived polyphenols (for example, catechin and its isotopic ingredients) against S. aureus or P. aeruginosa (5 log CFU/mL) [ 232 , 233 ].…”
Section: Hurdle Technologymentioning
confidence: 96%
“…A recent study demonstrated that antimicrobial technique based on photooxidation of caffeic acid was highly effective against biofilm-forming Streptococcus mutans , the most common acidogenic bacterial species isolated from human cariogenic dental plaques, in relation to ·OH formation (Nakamura et al, 2017 ). Therefore, the authors concluded that photoirradiation of caffeic acid has the potential to be applied as an inexpensive antimicrobial therapy to prevent and treat dental caries.…”
Section: Bactericidal Activity Of Photoirradiation Of Gpementioning
confidence: 99%